Uma análise da tradução de vocábulos relacionados à violência e criminalidade presentes em três obras de Patrícia Melo - Silva, Elisangela Fernandes Martins Parreira da [UNESP] (2014)
In this thesis we presented some results of a study that aimed to analyze the translation options adopted by Clifford Landers for the preferred and recurring words of Patrícia Melo, related to violence and crime, in The Killer (1997), Inferno (2002) and In praise of lies (1999) in relation to the respective original texts O matador (1995), Inferno (2000) and Elogio da mentira (1998). The theoretical approach is based on Corpus Based Translation Studies (Baker, 1993, 1995, 1996, 2004; Camargo, 2005, 2007) and Corpus Linguistics (Berber Sardinha, 2004). We also looked at the studies of Baker (1996) and Scott (1998) concerning normalization, in order to observe similarities and differences in the translation of Patricia Melo preferable words. The corpus was formed by the alignment of the original texts to their respective translations. For word extraction, we used tools provided by the WordSmith Tools program: WordList, KeyWords and Concord. The results obtainted present keywords that confirmed the theme of violence. In O matador, the following words and options of translations were found: matar kill; pó cocaine, coke and dust; revólver revolver, gun and by means of omissions; arma gun, firearm, police regulation pistol and weapon; and bandido bad guy, criminal, lowlife piece of scum and thief. In Inferno: morro hillside, hill, favela and omissions; traficante drug dealer, him, runner and drug trafficker; favela favela, hillside and omission; matar kill; tráfico drug traffic and traffic. In Elogio da mentira, the keywords were: cobra snake and boa; assassino murderer, killer, killing, assassin and deadly; matar kill; sucuri boa constrictor, boa and snake; and veneno venom and poison. The results also present a set of evidences which suggest the tendency of Clifford Landers to normalize the target text